Mitotic Catastrophe in BC3H1 Cells following Yessotoxin Exposure - Korsnes, Mónica Suárez; Korsnes, Reinert (Frontiers in Cell and Developmental Biology, 2017)
The marine toxin yessotoxin (YTX) can cause various cytotoxic effects depending on cell type and cell line. It is well known to trigger distinct mechanisms for programmed cell death which may overlap or cross-talk. The present contribution provides the first evidence that YTX can cause genotoxicity and induce mitotic catastrophe which can lead to different types of cell death. This work also demonstrates potential information gain from non-intrusive computer-based tracking of many individual cells during long time. Treatment of BC3H1 cells at their exponential growth phase causes atypical nuclear alterations and formation of giant cells with multiple nuclei. These are the most prominent morphological features of mitotic catastrophe. Giant cells undergo slow cell death in a necrosis-like manner. However, apoptotic-like cell death is also observed in these cells. Electron microscopy of treated BC3H1 cells reveal uncondensed chromatin and cells with double nuclei. Activation of p-p53, p-H2AX, p-Chk1, p-ATM and p-ATR and down-regulation of p-Chk2 indicate DNA damage response and cell cycle deregulation. Micronuclei formation further support this evidence. Data from tracking single cells reveal that YTX treatment suppresses a second round of cell division in BC3H1 cells. These findings suggest that YTX can induce genomic alterations or imperfections in chromosomal segregation leading to permanent mitotic failure. This understanding extends the list of effects from YTX and which are of interest to control cancer and tumour progression.